Hyperchloremia Is Associated With Complicated Course and Mortality in Pediatric Patients With Septic Shock*. Issue 2 (February 2018) - Stenson, Erin K.; Cvijanovich, Natalie Z.; Anas, Nick; Allen, Geoffrey L.; Thomas, Neal J.; Bigham, Michael T.; Weiss, Scott L.; Fitzgerald, Julie C.; Checchia, Paul A.; Meyer, Keith; Quasney, Michael; Hall, Mark; et al.
Abstract : Objective: Hyperchloremia is associated with poor outcome among critically ill adults, but it is unknown if a similar association exists among critically ill children. We determined if hyperchloremia is associated with poor outcomes in children with septic shock. Design: Retrospective analysis of a pediatric septic shock database. Setting: Twenty-nine PICUs in the United States. Patients: Eight hundred ninety children 10 years and younger with septic shock. Interventions: None. Measurements and Main Results: We considered the minimum, maximum, and mean chloride values during the initial 7 days of septic shock for each study subject as separate hyperchloremia variables. Within each category, we considered hyperchloremia as a dichotomous variable defined as a serum concentration greater than or equal to 110 mmol/L. We used multivariable logistic regression to determine the association between the hyperchloremia variables and outcome, adjusted for illness severity. We considered all cause 28-day mortality and complicated course as the primary outcome variables. Complicated course was defined as mortality by 28 days or persistence of greater than or equal to two organ failures at day 7 of septic shock. Secondarily, we conducted a stratified analysis using a biomarker-based mortality risk stratification tool. There were 226 patients (25%) with a complicated course and 93 mortalities (10%). Seventy patients had a minimum chloride greater than or equal to 110 mmol/L, 179 had a mean chloride greater than or equal to 110 mmol/L, and 514 had a maximum chloride greater than or equal to 110 mmol/L. A minimum chloride greater than or equal to 110 mmol/L was associated with increased odds of complicated course (odds ratio, 1.9; 95% CI, 1.1–3.2; p = 0.023) and mortality (odds ratio, 3.7; 95% CI, 2.0–6.8; p < 0.001). A mean chloride greater than or equal to 110 mmol/L was also associated with increased odds of mortality (odds ratio, 2.1; 95% CI, 1.3–3.5; p = 0.002). The secondary analysis yielded similar results. Conclusion: Hyperchloremia is independently associated with poor outcomes among children with septic shock. Abstract : Supplemental Digital Content is available in the text.